Alcohol-abuse drug disulfiram targets cancer via p97 segregase adaptor NPL4 - Skrott, Zdenek; Mistrik, Martin; Andersen, Klaus Kaae; Friis, Søren; Majera, Dusana; Gursky, Jan; Ozdian, Tomas; Bartkova, Jirina; Turi, Zsofia; Moudry, Pavel; Kraus, Marianne; Michalova, Martina; et al. (Nature, 2017)
Cancer incidence is rising and this global challenge is further exacerbated by tumour resistance to available medicines. A promising approach to meet the need for improved cancer treatment is drug repurposing. Here we highlight the potential for repurposing disulfiram (also known by the trade name Antabuse), an old alcohol-aversion drug that has been shown to be effective against diverse cancer types in preclinical studies. Our nationwide epidemiological study reveals that patients who continuously used disulfiram have a lower risk of death from cancer compared to those who stopped using the drug at their diagnosis. Moreover, we identify the ditiocarb-copper complex as the metabolite of disulfiram that is responsible for its anti-cancer effects, and provide methods to detect preferential accumulation of the complex in tumours and candidate biomarkers to analyse its effect on cells and tissues. Finally, our functional and biophysical analyses reveal the molecular target of disulfiram's tumour-suppressing effects as NPL4, an adaptor of p97 (also known as VCP) segregase, which is essential for the turnover of proteins involved in multiple regulatory and stress-response pathways in cells.
Keywords: Alcohol Deterrents; Alcoholism; Humans; přehodnocení terapeutických indikací léčivého přípravku; lidé středního věku; Proteolysis; Copper; Protein Binding; Molecular Targeted Therapy; Drug Repositioning; Dánsko; Female; dospělí; reakce na tepelný šok; Antineoplastic Agents; proteinové agregáty; jaderné proteiny; lidé; Disulfiram; zvířata; myši; proteolýza; Protein Aggregates; Mice; měď; Adult; Heat-Shock Response; ženské pohlaví; Male; Middle Aged; Denmark; disulfiram; Nuclear Proteins; alkoholismus; Neoplasms; cílená molekulární terapie; vazba proteinů; protinádorové látky; nádory; Animals; mužské pohlaví; odvykací prostředky alkoholu